DENTAL TISSUES STEM CELLS - Геращенко, С. Б.; Чайковський, Ю. Б.; Дєльцова, О. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The review of the literature is devoted to analysis of results of modern researches of stem cells of the adult person which contain in parodеntium. The stem niches of this site are surveyed. The opinion of scientists on dental stem cells properties for connecting, muscular and nervous tissues renewal. Potential stem cells opportunities for an regeneration of a tissues of tooth, periodontium and bone of an alveolus in clinic are discussed.